HUBUNGAN RELIGIUSITAS DENGAN PERILAKU BULLYING PADA PESERTA DIDIK DI SD NEGERI CIHEULEUT 2 KOTA BOGOR - Neng Sahibah Tu’sadiyah; Rifan Dainuri; Zahro Malihah (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2025)
Education has a very important role in shaping the character and behavior of students. The goals of education have been clearly set out in legislation No. 20 of 2003, but there are many problems to implement them. Bullying behavior in elementary schools is one of the main problems that is still often faced. therefore this study focuses on finding factors for bullying behavior, namely the relationship between religiosity and bullying behavior. This research uses quantitative methods, namely research methods that use numbers and statistics with the help of questionnaires and processing using excel and SPSS. Translated with DeepL.com (free version)This research was conducted at SD Negeri Ciheuleut 2, Bogor City, from June to August 2024. The sample in this study were 45 fifth grade students of SDN Ciheuleut 2. Data was collected by observation and with the help of questionnaires and documentation. In the results of this study, it can be seen that in the religiosity variable, 53 percent are in the high category, the rest are in the medium category. In the bullying variable, the results showed that 98 percent were in the low category, In the results of the correlation test in this study, the religiosity variable did not correlate with bullying behavior. The results of this study can be concluded that from the results obtained that it produces a Sig (2-tailed) value of -0.50> 0.05, which means that there is no relationship or relationship between the religiosity variable and the bullying variable. Researchers in this study suggest that in future studies to be able to see the relationship and influence of the level of bullying behavior based on other factors.